Evaluasi Pembelajaran Geografi Melalui Media Reuse Whiteboard Untuk Mendukung Pembangunan Berkelanjutan - Marlina Marlina (Geosfera: Jurnal Penelitian Geografi, 2025)
Appropriate learning evaluation is essential to assess the learning process including geography learning. The use of reuse whiteboard media can help in making value-based decisions by utilizing information collected through measurement and assessment. This study aims to determine how the use of reuse whiteboard media in the evaluation of geography learning with the aim of reducing paper waste and restoring students' writing skills that have not been honed for a long time. This research method uses the Research and Development (RD) method in the context of sustainable development with whiteboard media aimed at developing innovative products that are environmentally friendly, efficient, and in accordance with the principles of sustainability. This research was conducted at MAN 1 Majene, South Sulawesi, the research sample was by using the accidental sampling method. The results of the study showed that the use of Reuse Whiteboard as an alternative evaluation media has proven effective in reducing paper waste and supporting a more environmentally friendly teaching and learning process. The results of the trial showed that 4 out of 6 students (67%) felt the effectiveness of this media in evaluation and ease of use, while 33% felt it was less effective and had difficulty due to limited space to answer and additional waste from tissues.